Composition of Volatiles from Three Iris Species of Turkey - Baser, Kemal H. C.; Demirci, Betul; Orhan, Ilkay Erdogan; Kartal, MURAT; KARTAL, MURAT; Sekeroglu, Nazim; Sener, Bilge (My University, 2011)
The genus Iris is known to contain gorgeous flowers with a violet-like scent. Iris is represented in the Turkish flora by 37 species. Nonetheless, no study has been so far performed on the volatile constituents of the Turkish Iris species. In this study, our objective was to determine compositions of volatiles of the individual plant parts, including flowers, rhizomes, and sterns of three Turkish Iris species, namely: I. pseudacorus L. collected from two different localities (Beysehir and Trabzon), I. kerneriana Asch. & Sint. ex Baker, as well as I. sofarana Foster (cultivated) by microdistillation. The volatile compounds of these species were analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS) systems, simultaneously. The main components were characterized as follows: I. pseudacorus flowers: hexadecanoic acid (30.3%), heptacosane (13.6%), 6-methyl-5-hepten-2-one (11%); I. pseudacorus rhizomes: nonacosane (37.3%), triacontane (9.0%), octacosane (7.9%), pentacosane (7.7%); I. kerneriana flowers: a-kessyl acetate (14.7%), longipinene (10.8%), decanoic acid (10.6%), heptacosane (10.2%), hexadecanoic acid (9.5%), 6-methyl-5-hepten-2-one (7.1%); I. kerneriana rhizomes: tetradecanoic acid (31.5%), heptacosane (10.0%), alpha-kessyl acetate (9.5%), nonacosane (8.8%), 6-methyl-5-hepten-2-one (7.7%); I. kerneriana sterns: nonacosane (18.3%), heptacosane (16.7%), pentacosane (10.3%), tricosane (6.0%); I. pseudoacarus rhizomes: nonacosane (26.2%), alpha-Kessyl acetate (14.7%), triacontane (7.3%), octacosane (7.4%); I. pseudacorus sterns: octyl acetate (32.0%), nonacosane (14.4%), octyl butyrate (9.5%); I. sofarana rhizomes: decanoic acid (11.7%), alpha-pinene (8.4%), ethyl oleate (7.6%), irone (5.7%).